2017
DOI: 10.5815/ijitcs.2017.11.02
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation on the Impact of Trust Mediated Determinants and Moderating Factors on the Adoption of Cloud Computing

Abstract: Abstract-In a prior study we found out that trust is an effective factor in the acceptance and adoption of cloud computing using the UTAUT. However, various relationships from the original UTAUT were not confirmed in the extended model for cloud computing. Therefore, we present here a study aimed at investigating the mediation effect of trust on users' attitude toward the adoption of cloud computing using UTAUT. It is also aimed to examine the role of five moderating factors which are gender, age, education, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Según este modelo, se alienta a los ciudadanos a formar parte de las actividades oficiales del gobierno al participar en actividades como votación, encuestas, grupos comunitarios y debates. Por otra parte, Alharbi (2016) propone un nuevo tipo de GE, para completar cuatro tipos, los cuales son determinados por las necesidades del usuario final. El nuevo tipo es:…”
Section: Tipos De Gobierno Electrónicounclassified
“…Según este modelo, se alienta a los ciudadanos a formar parte de las actividades oficiales del gobierno al participar en actividades como votación, encuestas, grupos comunitarios y debates. Por otra parte, Alharbi (2016) propone un nuevo tipo de GE, para completar cuatro tipos, los cuales son determinados por las necesidades del usuario final. El nuevo tipo es:…”
Section: Tipos De Gobierno Electrónicounclassified
“…Previous studies suggested that perceived trust is positively impacted by effort expectancy [19,20]. However, in another study, it was found that effort expectancy did not affect perceived trust [18].…”
Section: Effort Expectancy To Intention To Buy and Perceived Trustmentioning
confidence: 79%
“…Performance expectancy, according to Venkatesh, is the degree to which a person believes that using the system would improve his performance at work [15]. According to earlier studies, performance expectations have a favorable impact on perceived trust [18][19][20]. Another study found that performance expectations have a positive impact on purchasing intentions [20,21].…”
Section: Performance Expectancy To Intention To Buy and Perceived Trustmentioning
confidence: 99%
“…Prior research applied various theories to the context of CC adoption, depending on the focus of the investigation. One stream of research employed the technology acceptance model (TAM) [14] to CC in various studies [e.g., [15][16][17] or its extension, the Unified Theory of Acceptance and Use of Technology (UTAUT) [18]. Studies relying on TAM and UTAUT focus on the individual choice level without involving organizational behavior and managerial decision processes [19].…”
Section: Technological Frames Of References (Tfr)mentioning
confidence: 99%
“…Studies relying on TAM and UTAUT focus on the individual choice level without involving organizational behavior and managerial decision processes [19]. Additionally, UTAUT proved not always useful in empirically confirming anticipated relationships [18].…”
Section: Technological Frames Of References (Tfr)mentioning
confidence: 99%